Maritime Security in an Era of Geopolitical Rivalry: Strategic Implications of Great Power Competition in Indo-Pacific Sea Lanes - Pandoe, Ridha Munawir Masly; Setiawibawa, Rachmat; Hutabarat, Harri Dolli; Saputro, Guntur Eko; Prakoso, Lukman Yudho (Jurnal Indonesia Sosial Sains, 2026)
The escalating geopolitical rivalry between major powers, particularly the United States and China, has profoundly reshaped the maritime security landscape of the Indo-Pacific region. Strategic sea lanes, such as the Strait of Malacca and the South China Sea, have become central arenas for this competition, creating a volatile, uncertain, complex, and ambiguous (VUCA) environment with direct implications for regional stability. This study analyzes the impact of this great power competition on Indonesia's maritime security and formulates an optimal national strategy. Employing a qualitative approach, the research utilizes a SWOT analysis strengthened by Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. The findings reveal that Indonesia is positioned in Quadrant I of the SWOT matrix, indicating significant internal strengths and substantial external opportunities. Consequently, a Strength-Opportunity (SO) strategy emerges as the most optimal choice. This strategy advocates for Indonesia to leverage its geostrategic position and diplomatic capital to lead regional cooperation, enhance maritime domain awareness through technology, and pursue adaptive defense diplomacy, thereby maintaining the stability of strategic sea lanes amidst great power rivalry.